(untitled) (Scientific journal of the Fergana State University, 2024)
The article discusses the advantages of using theatrical techniques in developing students’ speaking skills. Examples of using drama clubs in practice are provided. The unique features of theatrical technologies in foreign language learning and their impact on students are presented.